Temperature dependence of poloxamer insertion into and squeeze-out from lipid monolayers - Frey, Shelli L (Langmuir : the ACS journal of surfaces and colloids, 2007)
F68, a triblock copolymer of the form poly(ethylene oxide)-poly(propylene oxide)-poly(ethylene oxide), is found to effectively seal damaged cell membranes. To better understand the molecular interaction between F68 and cells, we have modeled the outer leaflet of a cell membrane with a dipalmitoylphosphatidylcholine (DPPC) monolayer spread at the air-water interface and introduced poloxamer into the subphase. Subsequent interactions of the polymer with the monolayer either upon expansion or compression were monitored using concurrent Langmuir isotherm and fluorescence microscopy measurements. To alter the activity of the poloxamer, a range of subphase temperatures from 5 to 37 degrees C was used. Lower temperatures increase the solubility of the poloxamer in the subphase and therefore lessen the amount of material at the interface, resulting in a lower equilibrium spreading pressure. Additionally, changes in temperature affect the phase behavior of DPPC. Below the triple point, the monolayer is condensed at pertinent polymer insertion pressures; for temperatures immediately above the triple point, the monolayer is a heterogeneous mix of liquid expanded and condensed phase; for the highest temperature measured, the DPPC monolayer remains completely fluid. At all temperatures, F68 inserts into DPPC monolayers at its equilibrium spreading pressure. Upon compression of the monolayer, polymers are squeezed-out at surface pressures notably higher than those for insertion, with higher temperatures leading to a higher squeeze-out pressure. An increase in temperature decreases the solvent quality of water for the poloxamer, lowering solubility of the polymer in the subphase and thus increasing its propensity to be maintained within the monolayer to higher pressures